A comparison study of perceived stress and quality of life among Master of Pharmacy and non-pharmacy master's students - Awadh, Ammar Ihsan Jawad; Aziz, Noorizan Abdul; Yaseen, Saramd Nabhan; S.A., Abdulameer; M.N, Sahib; O.Q.B, Al-Lela (International Pharmaceutical Federation (FIP), 2013)
Background: Postgraduate students often live with an excessive amount of stress, which can have negative academic, emotional and health-related outcomes.Aim: To examine perceived stress and health-related quality of life (HRQOL) among Master of Pharmacy (MPharm) students compared to non-pharmacy master's students (Non-MPharm). Method: The Perceived Stress Scale (PSS), SF-12v2 survey and a questionnaire instruments were used to measure stress, HRQOL and factors that MPharm students believed produced and alleviated stress, respectively. Results: One hundred percent of MPharm students (n=26) and 88% of Non-MPharm students (n=100) participated in this study. The mean PSS scores were insignificantly different between the MPharm students and Non-MPharm students. Negative correlations were found between stress and mental and physical HRQOL in MPharm students. However, only negative correlation between stress and mental HRQOL in Non-MPharm students. Conclusion: MPharm students reported relatively lower levels of stress and mental HRQOL than Non-MPharm students did.